A systematic review of total arthroplasty and arthrodesis for end-stage hallux rigidus: A biomechanical perspective. (December 2021) - Rajan, Rohan; Mishra, Arya
Highlights: Studies employing gait analysis for two treatments for hallux rigidus were sought. Heterogeneity was noted among studies and a narrative review was undertaken. Knowledge gaps and inconsistent results were identified with both the procedures. High powered, prospective, comparative studies are required. Abstract: Background: Both arthrodesis and total arthroplasty are acceptable surgical options for end stage hallux rigidus without significant angular deformity. Total arthroplasty preserves first metatarsophalangeal joint (MTPJ) motion, which may help restore a more physiological gait pattern. Research question: Is there a difference in the findings of gait studies after 1st MTPJ total arthroplasty or arthrodesis for end-stage hallux rigidus? Methods: PRISMA guidelines were followed to conduct a systematic review of literature for studies reporting gait analysis after the above procedures. Predetermined criteria were used to select papers and evaluated the findings of kinematic (spatial-temporal and dynamic motion), kinetic and foot pressure (pedobarographic) studies. Results: 12 titles were short-listed for synthesis. There was 1 randomized controlled trial comparing the two procedures. Among the remaining cohort studies, 5 reported on total arthroplasty and 6 on arthrodesis of the 1st MTPJ. Due to significant heterogeneity, a narrative synthesis was undertaken. No studies in the arthroplasty group reported spatial-temporal or kinetic parameters. Only 2 papers, 1 in each group, recorded motion within the foot. One of them showed preserved dynamic motion at the 1st MTPJ after total arthroplasty. Pedobarographic studies had discordant findings in studies within both groups regarding restoration of weight bearing through the medial forefoot and the pulp of the great toe during gait. Conclusion: Currently available studies are heterogenous and report inconsistent findings, which do not convincingly answer our research question. Prospective comparative studies with a large sample size, using standardized methodology in accredited laboratories with detailed reporting of kinetic, kinematic and pedobarographic components of gait analysis are required in order to draw concrete conclusions.